2022
DOI: 10.1021/acs.nanolett.2c03147
|View full text |Cite
|
Sign up to set email alerts
|

Double-Cavity Modulation of Exciton Polaritons in CsPbBr3 Microwire

Abstract: The lead halide perovskite has become a promising candidate for the study of exciton polaritons due to their excellent optical properties. Here, both experimental and simulated results confirm the existence of two kinds of Fabry−Peŕot microcavities in a single CsPbBr 3 microwire with an isosceles right triangle cross section, and we experimentally demonstrate that confined photons in a straight and a folded Fabry−Peŕot microcavity are strongly coupled with excitons to form exciton polaritons. Furthermore, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Similarly, the same conclusion was obtained in the other CsPbBr 3 microwire with W ∼ 2.8 and 5.3 μm (Supporting Information, Figure S4). The E – k ⊥ dispersion relationship of polaritons is obtained by using the dielectric function model, as shown in Figure d (Supporting Notes of the Supporting Information, the E – k ⊥ dispersion of polaritons). ,,, The Rabi splitting energy ( ℏ Ω) of the U-cavity polaritons is about 60 meV higher than that of the V-cavity polaritons, which may be related to the oscillator strength and the mode volume (Supporting Information, Figure S5). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, the same conclusion was obtained in the other CsPbBr 3 microwire with W ∼ 2.8 and 5.3 μm (Supporting Information, Figure S4). The E – k ⊥ dispersion relationship of polaritons is obtained by using the dielectric function model, as shown in Figure d (Supporting Notes of the Supporting Information, the E – k ⊥ dispersion of polaritons). ,,, The Rabi splitting energy ( ℏ Ω) of the U-cavity polaritons is about 60 meV higher than that of the V-cavity polaritons, which may be related to the oscillator strength and the mode volume (Supporting Information, Figure S5). …”
Section: Resultsmentioning
confidence: 99%
“…From the RE spectra in Figure S7, it can be similarly concluded that the ΔE increases gradually with the decrease of the W. Figure 2c,d shows the linear relationship between ΔE and 1/W at the dashed lines in Figure 2a,b, respectively, which demonstrates that resonators are created along the light propagation channels shown as the arrows in Figure 1a,b. According to the group refractive index 27,32 n g = hc/(2LΔE), where L is the effective length of the resonator (i.e., the W or the S). When the energy falls from 2.330 to 2.270 eV, the n g of the V-cavity reduces from 7.4 to 4.3, and the n g of the U-cavity decreases from 10.3 to 7.7.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations